Hepatic Response to the Interaction Between Thymoquinone and Iron-Dextran: an In Vitro and In Vivo Study - Ghasemi, Farzad; Ghaffari, Fatemeh; Omidifar, Navid; Azandaryani, Masoumeh Taheri; Nili-Ahmadabadi, Amir (Springernature, 2023)
Iron is one of the most important essential elements for cell function. However, iron overload can exert destructive effects on various tissues, especially the liver. The present study was designed to evaluate the effect of thymoquinone (TQ) on hepatotoxicity induced by iron-overload in in vitro and mouse model. After in vitro studies, thirty mice were divided into five groups, six each. Group 1 received normal saline. Group 2 received five doses of iron dextran (i.p; 100 mg/kg, one dose every 2 days). Group 3 received TQ (orally, 2 mg/kg/day). Groups 4 and 5 were administrated iron dextran saline (i.p; 100 mg/kg, one dose every 2 days) following treatment with 0.5 and 2 mg/kg/day of TQ, respectively. Based on the findings of the DPPH experiment, although TQ has significant anti-radical potential, at a safe dose of 15 x 10(+3) nM, it reduced the IC50 of iron dextran on HepG2 cells by about 25%, in in vitro. Following administration of low-dose TQ (0.5 mg/kg), a significant improvement was observed in serum hepatic enzymes activity and hepatic lipid peroxidation compared to iron dextran. However, administration of TQ-high dose (2 mg/kg) led to decrease antioxidant defense alongside increased serum hepatic enzymes and pathological damages in iron dextran-treated animals. Due to the different efficacy of TQ in treatment groups, it seems that the TQ therapeutic index is low and does not have significant safety in the iron overload status.
Keywords: Thymoquinone; Iron; Hepatotoxicity; Oxidative stress